Penurunan Nyeri Dismenore Menggunakan Kompres Hangat - Dahliana Dahliana; Suprida Suprida; Yuliana Yuliana (Journal of Complementary in Health, 2021)
Background: Painful menstruation or dysmenorrhea is one of the largest problems is the reason for the decline in activity of women during menstruation, for example, do not go to school. According to data from the World Health Organization (WHO) found the incidence of 1,769,429 people (90%) of women with dysmenorrhoea by 10-15% experienced severe dysmenorrhoea. Handling this issue by way of non-pharmacological needs to be developed for example with warm compresses. The purpose of this study to determine the effect of a warm compress to the decrease in the Young Women Dysmenorrhea in junior high school sriguna Palembang. Method: This type of research that is pre-experimental design One group pre and post test. Samples were obtained based on inclusion and exclusion criteria, amounting to 35 people. Results:Data obtained through observation sheets in the form of scale Numerical Rating Scale (NRS). Of the 35 respondents before the intervention is given by 26 respondents (74.3%) had moderate pain during menstruation and 9 respondents (25.7%) had mild pain during menstruation and after a given intervention as much as 21 respondents (60.0%) be no pain and 12 respondents (34.3%) to mild pain. Data were analyzed Wilcoxon. The p-value indicates that there is a significant association between a warm compress to the reduction in pain intensity (p value = 0.00). Based on these results it can be concluded that a warm compress dysmenorrhea effect to the decrease in the Young Women in junior Sriguna Palembang 2018. Conclusion: The influence of warm compresses impairment dismenore.further research is expected to do more research on the influence of a warm compress to the reduction of dysmenorrhea.